Ghost Wars : The Secret History of the CIA, Afghanistan, and Bin Laden, From the Soviet Invasion to September 10, 2001 - Coll, Steve (London Penguin Books, 2005)
"Comprehensively and for the first time, Pulitzer Prize-winning journalist Steve Coll tells the secret history of the CIA's role in Afghanistan, including its covert program against Soviet troops from 1979 to 1989, and examines the rise of the Taliban, the emergence of bin Laden, and the secret efforts by CIA officers and their agents to capture or kill bin Laden in Afghanistan after 1998. Based on extensive firsthand accounts, Ghost Wars is the inside story that goes well beyond anything previously published on U.S. involvement in Afghanistan. It chronicles the roles of midlevel CIA officers, their Afghan allies, and top spy masters such as Bill Casey, Saudi Arabia's Prince Turki al-Faisal, and George Tenet. And it describes heated debates within the American government and the often poisonous, mistrustful relations between the CIA and foreign intelligence agencies."--Jacket.
Include Index
"Updated with new documents from the 9/11 Commission"--Cover
Keywords: Bin Laden, Osama, 1957-2011 -- Afghanistan -- United States. Central Intelligence Agency